Eco-guilt in tourism: Do tourists intend to behave environmentally friendly and still revisit?. (June 2021) - Bahja, Frida; Hancer, Murat
Abstract: Although the role of (eco)guilt is relatively well-established in the literature on environmentally-friendly behaviors, little empirical research has been dedicated to this topic in tourism. Nevertheless, this topic has been gaining special interest in a spate of recent publications on tourists' (eco)guilt worldwide. A natural question arises: What is the influence of (eco)guilt in the context of environmentally-friendly tourism behavior (EFTB) and how does it effect tourists' revisiting intention? To answer this question, data were collected via Amazon Mechanical Turk (MTurk) through a convenience sampling method. The hypothesized relationships were analyzed with structural equation modeling (SEM). The results of this study provide empirical evidence that (eco)guilt's effect on EFTB is significant and positive. Altogether, environmental concerns, environmental knowledge, and (eco)guilt explain more than three-quarters of EFTB variance. Regarding the persistent assumption of (eco)guilt's negative impact on revisiting intention, the results show that this direct relationship is insignificant. Instead, the indirect effect of (eco)guilt reveals itself to be positive and significant through EFTB. Implications of this study in tourism literature are outlined, along with its insights for tourism managers and marketers. Highlights: (Eco)guilt stimulates environmentally friendly tourism behaviors (EFTB). Tourists' revisiting intentions (RI) are not endangered by (eco)guilt. Through EFTB, (eco)guilt has a desirable indirect effect on tourists' RI. EFTB and (eco)guilt remain limited in explaining the variance of tourists' RI. Strategic use of (eco)guilt appeals is encouraged for tourism marketers.